Analisis Struktur Aset Dalam Mengukur Aktivitas Dan Profitabilitas Perusahaan - Gia Tamara Sukandi; Nor Norisanti; Acep Samsudin (BUDGETING : Journal of Business, Management and Accounting, 2020)
This study aims to determine the analysis of asset structure in measuring the activity and profitability of the household appliances sub sector listed on the IDX. This study uses descriptive quantitative method, secondary data in the form of financial statements of household appliances sub-sector 2015 to 2017. The analysis used is horizontal analysis to measure asset structure, accounts receivable turnover (RTO), inventory turnover (ITO), working capital turnover ( WCTO), fixed asset turnover (FATO), total asset turnover (TATO), asset return (ROA) and using industry standard averages. The results showed that for three periods PT. Integra Indocabinet Tbk has increased its assets and profits. Whereas PT. Chitose Internasional Tbk and PT. Kedaung Indah Can Tbk experienced a fluctuation in assets, and an increase in profit. PT. Langgeng Makmur Industri Tbk experienced a decline in assets and profits. Conclusion, the company that is said to be good is a company that exceeds the industry average. While companies with low values ​​are due to the value obtained does not always exceed the average industry standard. Keywords: Activity, Asset Structure, and Company Profitability